Autologous Platelet‐Rich Fibrin in the Treatment of 3‐Wall Intrabony Defects in Aggressive Periodontitis: A Randomized Controlled Clinical Trial. Issue 11 (1st November 2017) - Bajaj, Pavan; Agarwal, Esha; Rao, Nishanth S.; Naik, Savitha B.; Pradeep, A.R.; Kalra, Nitish; Priyanka, N.; Kumari, Minal
Abstract : Background: Platelet‐rich fibrin (PRF) has recently been applied in osseous regeneration. The aim of the present study is to explore the efficacy of PRF in treatment of intrabony defects (IBDs) in aggressive periodontitis. Methods: Fifty‐four IBDs in 17 patients were treated either with autologous PRF with open flap debridement (OFD) or OFD alone. Clinical and radiologic parameters such as probing depth (PD), clinical attachment level (CAL), IBD depth, and percentage defect change were recorded at baseline and 9 months postoperatively. Results: Mean PD reduction and mean CAL gain were significantly greater in PRF compared with the control group. Furthermore, a significantly greater percentage of mean bone defect change was found in the PRF group. Conclusion: Within the limits of the present study, there is greater bone fill at sites treated with PRF with conventional OFD than conventional OFD alone.